FREE CONVECTION PROBLEMS OF NON-NEWTONIAN FLUID IN A VERTICAL CHANNEL WITH WALL TEMPERATURE IN THE PRESENCE OF HEAT SOURCE - Hanchinal, Manjula M. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
A The natural convection heat transfer of liquid metals in a confined enclosure is considered an important problem to passive cooling system. Natural convection in an enclose field with fluid-saturated porous medium.